PENGARUH COVID-19 TERHADAP HARGA DAN RETURN SAHAM (Studi Empiris Pada Perusahaan Sektor Kesehatan Yang Terdaftar di Bursa Efek Indonesia) - Khumairoh Ulin Nihayah; Anik Malikah; Hariri Hariri (Universitas Islam Malang, 2021)
This study aims to determine the effect of the COVID-19 pandemic on stock prices and stock returns in health sector companies listed on the IDX. Quantitative research method with the type of research is explanatory research. The population in this study were 12 health sector companies listed on the Indonesia Stock Exchange (IDX) and a sample of 10 companies was obtained using purposive sampling technique. The results in this study indicate that the Covid-19 pandemic through sales growth proxies has no effect on stock prices and the Covid-19 pandemic through sales growth proxies affects stock returns for the observation period in the second quarter of 2020 - first quarter of 2021 in health sector companies listed on the IDX. Keywords: Covid-19 pandemic, sales growth, stock prices and stock returns.